Elements of a quality pre-service teacher mentor: A literature review. (June 2020) - Ellis, Neville John; Alonzo, Dennis; Nguyen, Hoa Thi Mai
Abstract: This study reports on a review of contemporary literature which focuses on elements of a quality pre-service teacher mentor. For this purpose, seventy peer-reviewed publications were reviewed and analysed. A typology consisting of 53 indicators and seven dimensions was developed based on the findings. Our study contributes to the knowledge on the quality mentoring of pre-service teachers. It also provides the authors with the groundwork for developing a set of standards that describe the key elements of a quality mentor of pre-service teachers. Highlights: Mentors play a critical role in preparing teachers. A set of standards which describe the elements of a quality mentor are lacking. A quality mentor should develop a professional knowledge in mentoring. A quality mentor should support the pre-service teacher to nurture a teacher-identity. A quality mentor should relate learning to teacher professional standards.